2017
DOI: 10.1021/acsami.7b00260
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening for Design of Optimal Coating Materials to Suppress Gas Evolution in Li-Ion Battery Cathodes

Abstract: Ni-rich layered oxides are attractive materials owing to their potentially high capacity for cathode applications. However, when used as cathodes in Li-ion batteries, they contain a large amount of Li residues, which degrade the electrochemical properties because they are the source of gas generation inside the battery. Here, we propose a computational approach to designing optimal coating materials that prevent gas evolution by removing residual Li from the surface of the battery cathode. To discover promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…have proposed a computational approach to design optimal coating materials that can prevent the gas evolution of Ni‐rich cathodes by removing surface residual Li. [ 49 ] They have systematically compared the reactivity of 16 metal phosphates and 45 metal oxides with different Li residues such as Li 2 CO 3 and LiOH, and found that the reactivity of the coating materials containing 3d/4d transition metal elements is better than that of materials containing other types of elements. This study has established a selection rule for future coating materials to suppress gas evolution of Ni‐rich cathodes.…”
Section: The Degradation Pathway Of Ni‐rich Layered Cathodes Under Hamentioning
confidence: 99%
“…have proposed a computational approach to design optimal coating materials that can prevent the gas evolution of Ni‐rich cathodes by removing surface residual Li. [ 49 ] They have systematically compared the reactivity of 16 metal phosphates and 45 metal oxides with different Li residues such as Li 2 CO 3 and LiOH, and found that the reactivity of the coating materials containing 3d/4d transition metal elements is better than that of materials containing other types of elements. This study has established a selection rule for future coating materials to suppress gas evolution of Ni‐rich cathodes.…”
Section: The Degradation Pathway Of Ni‐rich Layered Cathodes Under Hamentioning
confidence: 99%
“…ii) The dissolution of TM ions and organic electrolyte decomposition starting from the electrode/electrolyte interface are engendered by the highly oxidized Ni 4+ ions during charge–discharge process, which is highly intensified due to the emergence of microcracks resulting from the anisotropic contraction and expansion . iii) The overcharged cathodes are susceptible to thermal decomposition, thus breaking down the TM‐O bonds and releasing oxygen from the host lattice . These detrimental cases preferentially take place at the surface/interface of highly delithiated electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, surface coating is one of the most widely used methods in laboratory investigation. Generally, surface coating layers can not only enhance the air-storage stability of Ni-rich cathode materials, but also protect Ni-rich cathode materials from HF corrosion and detrimental side [Min et al, 2017] with permission from American Chemical Society. (B) Schematic diagrams of the working mechanism of CNT& Li 3 PO 4 coating layer and cycling stability of CNT& Li 3 PO 4 coated sample compared to pristine and (C and D) SEM images of the CNT& Li 3 PO 4 coated sample.…”
Section: Surface Coatingmentioning
confidence: 99%
“…Moreover, the coating layers can be formed in-situ on the surface of Ni-rich cathode materials via chemical reactions between coating media and residual lithium compounds, which could eliminate surface impurities as well as form a functional film on the surface. For example, H 3 PO 4 (Jo et al, 2014a;Min et al, 2017;Yang et al, 2019c), an acidic coating media, can react with the residual lithium compounds, such as LiOH and Li 2 CO 3 to form a Li 3 PO 4 coating layer, which has been verified to effectively enhance the surface stability of Ni-rich cathode materials. Due to the reduced surface insulating impurities and high ionic conductivity of newly generated Li 3 PO 4 , the capacity retention and rate capability of Li 3 PO 4 -coated NCM622 are greatly improved (Jo et al, 2014a).…”
Section: Surface Coatingmentioning
confidence: 99%
See 1 more Smart Citation